Old age known and unknown - chosen reflections on contemporary old age - Elżbieta Dubas (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2014)
In the text the authoress has reflections on the state of scientific knowledge and social awareness of the topic of ageing process and old age. She particularly pays attention to the issues which are shown in an incomplete way and which should be the subject of further scientific studies and analyses. They include fragmentary knowledge of corporeality, mentality and spirituality of an elderly person, difficult existential topics, among them the experience of death and loneliness, issues requiring "verification", e.g. the cult of youth and outsideness, the needs of the elderly, care and help in old age, the role of a family, the attitude to development and activity, change and hurry, predictability and preparing for old age and also the so called gerontological taboo: denying old age and spirituality, pushing away the question of passing and transcendentalism, accompanying an elderly person in their journey. She shows the need of treating old age as value.